Preparation method of defect-state ZnIn2S4 / metal complex composite catalyst and application of defect-state ZnIn2S4 / metal complex composite catalyst in photocatalysis
By introducing defect states and metal complexes into ZnIn2S4, a composite catalyst is prepared, which solves the problem of low photocatalytic hydrogen production efficiency, achieves efficient photocatalytic reactions and significantly increases hydrogen production.
Patent Information
- Application Number
- CN202411430361.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
Among the existing photocatalytic hydrogen production technologies, the catalytic efficiency is low, mainly due to the low separation efficiency of photogenerated electrons and holes and the high energy barrier of surface redox reactions.
By introducing defective ZnIn2S4 nanosheets as carriers to anchor the metal complex, a defective ZnIn2S4/metal complex composite catalyst was prepared. This method not only improves the separation efficiency of photogenerated electrons and holes, but also reduces the surface reaction energy barrier and promotes efficient photocatalytic reactions.
The photocatalytic activity of ZnIn2S4 is significantly improved and the efficiency of the photocatalytic hydrogen production reaction is improved. The composite catalyst also shows good results in the fields of photocatalytic reduction of carbon dioxide and photolysis of water.
Smart Images

Figure CN119303630A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysis, and in particular relates to a preparation method of a defective ZnIn2S4 / metal complex composite catalyst and its application in photocatalysis. Background Art
[0002] With the continuous growth of global energy demand, the development and utilization of new energy has become an important direction for the development of countries around the world. Hydrogen energy has been widely regarded as an ideal green energy source due to its many advantages such as cleanliness and high energy density, and has been highly valued by countries around the world. Using solar energy to photocatalytically decompose water to produce hydrogen is a highly promising hydrogen production technology and has become one of the research hotspots in the international academic community. However, the current photocatalytic hydrogen production technology still faces the problem of low catalytic efficiency. The research and development of efficient photocatalysts is the core of catalytic technology.
[0003] ZnIn2S4 is a very promising photocatalytic semiconductor material. It has attracted much attention due to its excellent visible light absorption, unique photoelectrochemical properties, low toxicity and environmental friendliness. At present, various strategies have been adopted to modify ZnIn2S4 to improve its photocatalytic efficiency, such as heteroatom doping (copper-doped ZnIn2S4, oxygen-doped ZnIn2S4), heterostructure construction (Ni2P / ZnIn2S4, AgIn5S8 / ZnIn2S4), defect regulation, etc. Despite the above efforts, it still faces the problem of low catalytic efficiency. This is mainly because: (1) conventional modification strategies are difficult to achieve rapid and efficient separation of photogenerated electrons and holes, and the recombination of photogenerated carriers is still relatively serious; (2) the surface redox reaction energy barrier or overpotential is high, resulting in a slow catalytic reaction rate. Therefore, improving the separation efficiency of photogenerated carriers and reducing the energy barrier of surface redox reactions are the key to improving the efficiency of hydrogen production from water splitting by ZnIn2S4.
[0004] Metal complexes have the advantages of dispersed metal atoms, uniform active centers, continuously adjustable molecular structures, and good catalytic activity. Therefore, combining ZnIn2S4 and metal complexes to construct a ZnIn2S4 / metal complex composite system provides a new idea for solving the above problems. This composite system can combine the advantages of both ZnIn2S4 and metal complexes. ZnIn2S4 acts as a light harvester to generate photogenerated carriers, and the metal complex acts as a catalytic active center to complete the reduction reaction. The introduction of metal complexes can not only achieve rapid transfer of photogenerated carriers and greatly improve the separation efficiency of photogenerated electrons and holes in ZnIn2S4, but also the lower reaction energy barrier on the metal complexes promotes efficient surface reduction reactions. Summary of the invention
[0005] In view of the problems existing in the prior art, in order to improve the photocatalytic activity of ZnIn2S4, the present invention prepares a composite catalyst by introducing defective ZnIn2S4 nanosheets as carriers to anchor metal complexes, and provides a new research idea for solving the above problems. The present invention creatively introduces metal complexes, and the introduction of metal complexes can not only realize the rapid transfer of photogenerated carriers, but also greatly improve the separation efficiency of photogenerated electrons and holes in ZnIn2S4. The lower reaction energy barrier on the metal complex can also promote the efficient photocatalytic reaction. In addition, the present invention creatively prepares defective ZnIn2S4. On the one hand, the defective ZnIn2S4 semiconductor has a narrower band gap and a more negative conduction band potential, which is conducive to the generation of more photogenerated carriers, and is also conducive to the transfer of photogenerated electrons from the conduction band of ZnIn2S4 to the metal complex. On the other hand, the surface defects of ZnIn2S4 can not only regulate the separation and migration of photogenerated carriers, but also establish a charge transfer channel between ZnIn2S4 and the metal complex, and accelerate the interfacial charge transfer.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing a defective ZnIn2S4 / metal complex composite catalyst, wherein the composite catalyst is prepared by using defective ZnIn2S4 as a light harvesting agent and a metal complex as a catalytic center.
[0008] Furthermore, the preparation method of the defective ZnIn2S4 / metal complex composite catalyst comprises the following steps: synthesizing defective ZnIn2S4 by a solvothermal method; ultrasonically dispersing the defective ZnIn2S4 in water to obtain solution A, then dissolving the metal complex in water to obtain solution B, dripping solution B into solution A drop by drop and ultrasonically stirring until uniformly mixed, washing the obtained precipitate by centrifugation, and drying to obtain a composite catalyst, recorded as ZnIn2S4 / metal complex-X (X is the volume of solution B).
[0009] Furthermore, defective ZnIn2S4 nanosheets were prepared by a solvothermal method, and the preparation method was as follows: ZnCl2·4H2O, InCl3·4H2O and TAA were dissolved in a mixed solution of ethylene glycol and water, the molar ratio of ZnCl2·4H2O, InCl3·4H2O and TAA was 1:2:(2-8), the volume ratio of ethylene glycol and water was 1:1, and stirring was continued for 1 hour. Then, the mixture was transferred to a reactor and kept at 120°C for 12 hours. After the reactor was naturally cooled to room temperature, the precipitate was washed by centrifugation and dried in a vacuum drying oven at 65°C.
[0010] Furthermore, two metal complexes [Co(NH3)5Cl]Cl2 and [Ni(NH3)6]Cl2 were prepared by substitution reaction between CoCl2 solution and concentrated ammonia solution, and then the central Co(II) was oxidized to Co(III) by oxidant H2O2, and then substitution reaction was carried out with concentrated hydrochloric acid to prepare the complex [Co(NH3)5Cl]Cl2. A mixed solution of excess concentrated ammonia and ice water was added to the NiCl2 solution to prepare the complex Ni(NH3)6]Cl2.
[0011] The present invention also provides the use of the defective ZnIn2S4 / metal complex composite catalyst prepared by the preparation method in photocatalysis, wherein the photocatalysis includes photocatalytic reduction of carbon dioxide, photocatalytic hydrogen production, and photodegradation, with photocatalytic hydrogen production reaction being preferred.
[0012] Beneficial effects of the present invention: The present invention can not only greatly improve the separation efficiency of photogenerated electrons and holes in ZnIn2S4 by introducing metal complexes, but the lower reaction energy barrier on the metal complex can also promote the efficient photocatalytic hydrogen production reaction. In addition, the present invention prepares defective ZnIn2S4 by constructing defects in ZnIn2S4. The surface defects can not only regulate the separation and migration of photogenerated carriers, but also establish charge transfer channels between ZnIn2S4 and metal complexes to achieve rapid interface transfer of photogenerated carriers. The obtained defective ZnIn2S4 / metal complex composite catalyst can be used in the fields of photocatalytic reduction of carbon dioxide, photolysis of water, photodegradation, etc., with photocatalytic hydrogen production reaction being preferred. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 This is the XRD spectrum of the ZnIn2S4 / Ni metal complex composite catalyst prepared in Example 1.
[0015] Figure 2 This is the XRD spectrum of the ZnIn2S4 / Co metal complex composite catalyst prepared in Example 2.
[0016] Figure 3 These are the SEM and SEM-Mapping images of the ZnIn2S4 / Ni metal complex composite catalyst ZIS / Ni-5 prepared in Example 1.
[0017] Figure 4 These are the SEM and SEM-Mapping images of the ZnIn2S4 / Co metal complex composite catalyst ZIS / Co-5 prepared in Example 2.
[0018] Figure 5 A graph showing the variation of the photocatalytic hydrogen production of the ZnIn2S4 / Ni metal complex composite catalyst prepared in Example 1 with the loading amount of the Ni metal complex.
[0019] Figure 6 This is a graph showing the change in the photocatalytic hydrogen production of the ZnIn2S4 / Co metal complex composite catalyst prepared in Example 2 as a function of the Co metal complex loading amount.
[0020] Figure 7 Graphs showing photocatalytic hydrogen production of the catalysts prepared in Example 1, Example 2 and Comparative Example 1. Figure 8 Photocatalytic hydrogen production stability test diagram of the ZnIn2S4 / Ni metal complex composite catalyst ZIS / Ni-5 prepared in Example 1. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0022] Example 1
[0023] The preparation method of the defective ZnIn2S4 / Ni metal complex composite catalyst in this embodiment is as follows:
[0024] (1) Preparation of defective ZnIn2S4 nanosheets
[0025] ZnIn2S4 nanocatalyst was prepared by a solvothermal method using ZnCl2 as a zinc source, InCl3 as an indium source, TAA as a sulfur source and a mixed solution of ethylene glycol and water as a reaction medium: ZnCl2·4H2O, InCl3·4H2O and TAA were dissolved in a mixed solution of ethylene glycol and water, the molar ratio of ZnCl2·4H2O, InCl3·4H2O and TAA was 1:2:4, the volume ratio of ethylene glycol and water was 1:1, and stirring was continued for 60 minutes. Then, the mixture was transferred to a reactor and kept at 120°C for 12 hours. After the reactor was naturally cooled to room temperature, the precipitate was washed by centrifugation and dried in a vacuum drying oven at 65°C.
[0026] (2) Preparation of Ni metal complexes
[0027] 7.25 g NiCl2·6H2O was dissolved in 8 mL ice deionized water, and then 20 mL NH3·H2O was added dropwise. Finally, the product was centrifuged and dried in a vacuum oven at 65°C overnight to obtain the Ni metal complex [Ni(NH3)6]Cl2.
[0028] (3) Preparation of defective ZnIn2S4 / Ni composite catalyst
[0029] 84.5 mg ZnIn2S4 was dissolved in 30 mL of deionized water to form a uniform suspension A. 0.02 mmol (4.63 mg) [Ni(NH3)6]Cl2 was dissolved in 100 mL of deionized water to form solution B. Subsequently, different volumes of solution B (1, 5, 10, 100 mL) were added dropwise to suspension A, and the resulting mixture was stirred for 30 min. Finally, the product was obtained by centrifugation and dried overnight at 65 ° C in a vacuum oven. The obtained sample was recorded as ZIS / Ni-X (X is the volume of solution B, unit mL), that is, ZIS / Ni-1, ZIS / Ni-5, ZIS / Ni-10 and ZIS / Ni (the volume of solution B corresponding to ZIS / Ni is 100 mL).
[0030] Example 2
[0031] The preparation method of the defective ZnIn2S4 / Co composite catalyst in this embodiment is as follows:
[0032] (1) Preparation of defective ZnIn2S4 nanosheets
[0033] ZnIn2S4 nanocatalyst was prepared by a solvothermal method using ZnCl2 as a zinc source, InCl3 as an indium source, TAA as a sulfur source and a mixed solution of ethylene glycol and water as a reaction medium: ZnCl2·4H2O, InCl3·4H2O and TAA were dissolved in a mixed solution of ethylene glycol and water, the molar ratio of ZnCl2·4H2O, InCl3·4H2O and TAA was 1:2:4, the volume ratio of ethylene glycol to water was 1:1, and the mixture was stirred for 1 hour. The mixture was then transferred to a reactor and kept at 120°C for 12 hours. The reactor was cooled naturally to room temperature, the precipitate was washed by centrifugation, and dried in a vacuum drying oven at 65°C.
[0034] (2) Preparation of Co metal complexes
[0035] 4 g of cobalt chloride and 2 g of ammonium chloride were dissolved in 10 mL of deionized water, and then 12.5 mL of NH3·H2O was added dropwise to the solution. Subsequently, 6.5 mL of hydrogen peroxide and 25 mL of hydrochloric acid were further added to the solution. The resulting solution was kept in a 60°C water bath for 15 min. Finally, the product was obtained by centrifugation and dried in a vacuum oven at 65°C overnight to obtain the Co metal complex [Co(NH3)5Cl]Cl2.
[0036] (3) Preparation of defective ZnIn2S4 / Co metal complex composite catalyst
[0037] 84.5 mg ZnIn2S4 was dissolved in 30 mL of deionized water to form a uniform suspension A. 0.02 mmol (5 mg) [Co(NH3)5Cl]Cl2 was dissolved in 100 mL of deionized water to form solution B. Subsequently, different volumes of solution B (1, 5, 10, 100 mL) were added dropwise to suspension A, and the resulting mixture was stirred for 30 min. Finally, the product was obtained by centrifugation and dried overnight at 65 ° C in a vacuum oven. The obtained sample was recorded as ZIS / Co-X (X is the volume of solution B), namely, ZIS / Co-1, ZIS / Co-5, ZIS / Co-10 and ZIS / Co (the volume of solution B corresponding to ZIS / Co is 100 mL).
[0038] Comparative Example 1
[0039] The preparation method of the defective ZnIn2S4 catalyst is as follows:
[0040] ZnIn2S4 nanocatalyst was prepared by a solvothermal method using ZnCl2 as a zinc source, InCl3 as an indium source, TAA as a sulfur source and a mixed solution of ethylene glycol and water as a reaction medium: ZnCl2·4H2O, InCl3·4H2O and TAA were dissolved in a mixed solution of ethylene glycol and water, the molar ratio of ZnCl2·4H2O, InCl3·4H2O and TAA was 1:2:4, the volume ratio of ethylene glycol to water was 1:1, and the mixture was stirred for 1 hour. The mixture was then transferred to a reactor and kept at 120°C for 12 hours. The reactor was cooled naturally to room temperature, the precipitate was washed by centrifugation, and dried in a vacuum drying oven at 65°C.
[0041] Figure 1 and 2 2 are the XRD spectra of the defective ZnIn2S4 / Ni and ZnIn2S4 / Co composite catalysts prepared in Examples 1 and 2. From the results, it can be seen that the prepared composite catalysts do not contain impurities and are relatively pure.
[0042] Figure 3 and 4These are the SEM and EDS-Mapping images of the catalyst ZIS / Co-5 prepared in Example 1 and the catalyst ZIS / Co-5 prepared in Example 2. From the results, it can be seen that the Ni and Co metal complexes are uniformly loaded on the defective ZnIn2S4 nanosheets.
[0043] 1. Photocatalytic hydrogen production reaction
[0044] Prepare 100mL solution (90mL water and 10mL triethanolamine), weigh 40mg of the catalyst prepared in Examples 1-2 and Comparative Example 1, put it into the above solution, and ultrasonicate for half an hour to make the catalyst evenly dispersed in the solution. First, introduce Ar into the reaction system for about half an hour in the dark to remove the air in the system. Then, under the irradiation of a xenon lamp, the reduction product is detected by gas chromatography every 1 hour. The results are as follows: Figure 5-6 shown.
[0045] Figure 5 and 6 The figure is a graph showing the variation of the photocatalytic hydrogen production of the composite catalysts prepared in Examples 1 and 2 with the metal complex loading. It can be seen from the figure that with the increase of the metal complex loading, the photocatalytic hydrogen production first increases and then decreases, and when the volume of the metal complex solution is 5 mL, the photocatalytic hydrogen production is the highest.
[0046] Figure 7 The photocatalytic hydrogen production diagrams of the catalysts prepared in Example 1, Example 2 and Comparative Example 1. It can be seen that by introducing the metal complex, the photogenerated electrons and holes are effectively separated, and the photocatalytic hydrogen production activity is significantly improved compared with the single defective ZnIn2S4.
[0047] Figure 8 The photocatalytic hydrogen production stability test chart of the ZnIn2S4 / Ni metal complex composite catalyst prepared in Example 1 shows that the prepared composite catalyst exhibits good stability.
[0048] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a defective ZnIn2S4 / metal complex composite catalyst, characterized in that: A composite catalyst was prepared using defective ZnIn2S4 as a light-harvesting agent and a metal complex as a catalytic center.
2. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 1, characterized in that The following steps are involved: (1) Synthesis of defective ZnIn2S4 by solvothermal method; (2) Ultrasonic dispersion of defective ZnIn2S4 in water to obtain solution A, then dissolving the metal complex in water to obtain solution B, dripping solution B into solution A drop by drop and stirring until the mixture is uniform, washing the obtained precipitate by centrifugation, and drying to obtain a composite catalyst.
3. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 2, characterized in that: The preparation method of defective ZnIn2S4 is as follows: ZnCl2∙4H2O, InCl3∙4H2O and thioacetamide TAA are dissolved in a mixed solution of ethylene glycol and water, and the mixture is transferred to a reactor after continuous stirring for 1 hour for a hydrothermal reaction. After the reaction is completed, the reactor is allowed to cool naturally to room temperature, the precipitate is washed by centrifugation, and dried in a vacuum drying oven at 65°C to obtain defective ZnIn2S4.
4. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 2, characterized in that: The molar ratio of the ZnCl2∙4H2O, InCl3∙4H2O and TAA is 1:2:(2-8), and the volume ratio of the ethylene glycol and water is 1:
1.
5. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 120°C and the time is 10-20 h.
6. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claims 1 and 2, characterized in that: The metal complex is one of [Co(NH3)5Cl]Cl2 or [Ni(NH3)6]Cl2.
7. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 6, characterized in that: Two metal complexes [Co(NH3)5Cl]Cl2 and [Ni(NH3)6]Cl2 were prepared by substitution reaction of CoCl2 solution and NiCl2 solution with concentrated ammonia water.
8. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 7, characterized in that: Use CoCl2 and concentrated ammonia water to carry out substitution reaction, then use the oxidant H2O2 to oxidize the central Co(II) to Co(III), and then carry out substitution reaction with concentrated hydrochloric acid to prepare the complex [Co(NH3)5Cl]Cl2; add a mixed solution of excess concentrated ammonia water and ice water to the NiCl2 solution to prepare the complex Ni(NH3)6]Cl2.
9. The method for preparing the defective ZnIn2S4 / metal complex composite catalyst according to claim 2, characterized in that: The molar ratio of the metal complex and defective ZnIn2S4 is (0.001-0.1):
1.
10. Use of the defective ZnIn2S4 / metal complex composite catalyst prepared by the preparation method according to any one of claims 1 to 9 in photocatalysis, characterized in that: The photocatalysis includes photocatalytic reduction of carbon dioxide, photolysis of water, and photodegradation.